Macroeconomic regime and labor market: the Argentine experience of the past two decades - Beccaria, Luis; Maurizio, Roxana (Nova Economia, 2016)
This document analyzes the interactions between macroeconomic regimes, employment generation and the dynamics of labor incomes in Argentina under two different macroeconomic regimes: the currency board regime of the 1990s and the high real exchange rate regime that followed. The former, characterized by a strong currency overvaluation, had a negative impact on economic activity and the labor market. However, the maintenance of a competitive real exchange rate does not by itself guarantee the sustained positive performance of the labor market, as it became evident in Argentina during the 2000s. Although the sizable depreciation of the peso –together with a positive international context- favored the expansion of output and employment, the initial concern of maintaining the real exchange rate at a competitive level was not continued with policies aimed to counteract the appreciation trend that appeared a few years after the implementation of the new regime.